2014
DOI: 10.1042/bj20140598
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis reveals an essential role for high-affinity iron uptake system, haemolysin and CFEM domain-containing protein in iron homoeostasis and virulence in Candida glabrata

Abstract: Iron is an essential nutrient for all living organisms and human pathogens employ a battery of factors to scavenge iron from the high-affinity iron-binding host proteins. In the present study, we have elucidated, via a candidate gene approach, major iron acquisition and homoeostatic mechanisms operational in an opportunistic human fungal pathogen Candida glabrata. Phenotypic, biochemical and molecular analysis of a set of 13 C. glabrata strains, deleted for proteins potentially implicated in iron metabolism, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 55 publications
6
66
0
Order By: Relevance
“…2A, 13 iron homeostasis genes including genes encoding proteins involved in high-affinity iron uptake (CgFet3, a multicopper oxidase), lowaffinity ion transport (CgFet4, a low-affinity ion transporter), and siderophore-iron acquisition (CgSit1, a siderophore-iron transporter) were differentially regulated in the Cgvps34⌬ mutant. Of note, the high-affinity iron transport system in C. glabrata is activated and repressed under iron-depleted and iron-repleted conditions, respectively (10,19). Overall, our RNA-Seq analysis revealed that genes involved in iron transport were down-regulated, whereas genes implicated in iron utilization/iron-sulfur (Fe-S) cluster binding were up-regulated in the Cgvps34⌬ mutant ( Fig.…”
Section: Rna Sequencing Analysis Reveals Deregulation Of Iron Metabolmentioning
confidence: 78%
See 4 more Smart Citations
“…2A, 13 iron homeostasis genes including genes encoding proteins involved in high-affinity iron uptake (CgFet3, a multicopper oxidase), lowaffinity ion transport (CgFet4, a low-affinity ion transporter), and siderophore-iron acquisition (CgSit1, a siderophore-iron transporter) were differentially regulated in the Cgvps34⌬ mutant. Of note, the high-affinity iron transport system in C. glabrata is activated and repressed under iron-depleted and iron-repleted conditions, respectively (10,19). Overall, our RNA-Seq analysis revealed that genes involved in iron transport were down-regulated, whereas genes implicated in iron utilization/iron-sulfur (Fe-S) cluster binding were up-regulated in the Cgvps34⌬ mutant ( Fig.…”
Section: Rna Sequencing Analysis Reveals Deregulation Of Iron Metabolmentioning
confidence: 78%
“…low-affinity system composed of CgFet4, and the siderophore uptake system comprised of CgSit1 transporter, are required for iron acquisition (10). As shown in Fig.…”
Section: Rna Sequencing Analysis Reveals Deregulation Of Iron Metabolmentioning
confidence: 99%
See 3 more Smart Citations